Radially asymmetric gastroesophageal acid reflux in the distal esophagus : examinations with novel pH sensor catheter equipped with 8 pH sensors - Ohara, Shunji; Furuta, Kenji; Adachi, Kyoichi; Shimura, Shino; Fukazawa, Kousuke; Aimi, Masahito; Okamoto, Eisuke; Komazawa, Yoshinori; Kinoshita, Yoshikazu (Journal of gastroenterology, 2012)
Background Esophageal mucosal breaks in patients with Los Angeles (LA) grade A or B esophagitis are mainly found in the right anterior wall of the distal esophagus. The aim of this study was to reveal radial acid exposure in the distal esophagus and determine whether radial asymmetry of acid exposure is a possible cause of radially asymmetric distribution of the lesions. Methods We developed a novel pH sensor catheter using a polyvinyl chloride catheter equipped with 8 antimony pH sensors radially arrayed at the same level. Four healthy volunteers, 5 patients with non-erosive reflux disease (NERD), and 10 with LA grade A or B esophagitis were enrolled. The sensors were set 2 cm above the upper limit of the lower esophageal sphincter, and post-prandial gastroesophageal acid reflux was monitored for 3 h with the subjects in a sitting position. Results We successfully examined radial acid exposure in the distal esophagus in all subjects using our novel pH sensor catheter. Radial variations of acid exposure in the distal esophagus were not observed in the healthy subjects. In contrast, the patients with NERD and those with reflux esophagitis had radial asymmetric acid exposure that was predominant on the right wall of the distal esophagus. In the majority of patients with reflux esophagitis, the directions of longer acid exposure coincided with the locations of mucosal breaks. Conclusions Radial acid exposure could be examined using our novel 8-channel pH sensor catheter. We found that the directions of longer acid exposure were associated with the locations of mucosal breaks.